Induction and Transcription Studies of the Dextransucrase Gene in Leuconostoc mesenteroides NRRL B-512F - Quirasco, M. (American Society for Microbiology, 1999)
Dextransucrase production by Leuconostoc mesenteroides NRRL B-512F in media containing carbon sources other than sucrose is reported for the first time. Dextransucrases were analyzed by gel electrophoresis and by an in situ activity assay. Their polymers and acceptor reaction products were also compared by (13)C nuclear magnetic resonance and high-performance liquid chromatography techniques, respectively. From these analyses, it was found that, independently of the carbon source, L. mesenteroides NRRL B-512F produced dextransucrases of the same size and product specificity. The 5′ ends of dextransucrase mRNAs isolated from cells grown under different culture conditions were identical. Based on this evidence, we conclude that dextransucrases obtained from cells grown on the various carbon sources result from the transcription of the same gene. The control of expression occurs at this level. The low dextransucrase yields from cultures in d-glucose or d-fructose and the enhancement of dextransucrase gene transcription in the presence of sucrose suggest that an activating phenomenon may be involved in the expression mechanism. Dextransucrase mRNA has a size of approximately 4.8 kb, indicating that the gene is located in a monocistronic operon. The transcription start point was localized 34 bp upstream from the ATG start codon. The −10 and −35 sequences found, TATAAT and TTTACA, were highly homologous to the only glycosyltransferase promoter sequence reported for lactic acid bacteria.